Clonal propagation of vietnamese orthosiphon stamineus benth. accession containing high content of sinensetin using plant tissue culture technique - Long, Đinh Đoàn; Tú, Trần Tuấn; Hòa, Hoàng Thị; Chi, Trần Dụ; Huyền, Phạm Thanh; Thu, Nguyễn Bích (VNU Journal of Science: Natural Sciences and Technology, 2006)
Abstract